2018
DOI: 10.1371/journal.pone.0205804
|View full text |Cite
|
Sign up to set email alerts
|

Risk taking of educated nematodes

Abstract: Nematode parasites rely on successful host infection to perpetuate their species. Infection by individual nematode parasites can be risky, however; any one individual could be killed by the host’s immune response. Here we use a model system to show that environmental cues and parasite past experience can be used by entomopathogenic nematodes to reduce individual risk of infection. Past parasite experience can more than double the infective virulence (number of host invaders) of a given cohort of entomopathogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…Nematodes are well documented in the literature to survive exposure to these HIPVs ( Willett et al, 2015 ; Willet et al, 2017 ; Willet et al, 2018 ), and in this investigation no mortality of the IJs was observed after direct exposure of the IJs to the HIPVs It is likely that the mortality of the IJs was not arising from nematocidal properties of the HIPVs. Therefore, the increased mortality of the IJs was likely arising from interactions with the insect’s immune system.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Nematodes are well documented in the literature to survive exposure to these HIPVs ( Willett et al, 2015 ; Willet et al, 2017 ; Willet et al, 2018 ), and in this investigation no mortality of the IJs was observed after direct exposure of the IJs to the HIPVs It is likely that the mortality of the IJs was not arising from nematocidal properties of the HIPVs. Therefore, the increased mortality of the IJs was likely arising from interactions with the insect’s immune system.…”
Section: Discussionsupporting
confidence: 54%
“…For example, it has been demonstrated that exposure of EPNs to root produced terpenoids can result in enhanced movement of EPNs to the source of those terpenoids ( Ali et al, 2012 ; Willett et al, 2015 ). This movement of the EPNs towards the insect pest also results in increased infection/invasion of the pest by the EPNs ( Willett et al, 2015 ; Willett et al, 2018 ). These terpenoids are typically produced by the plants in response to insect herbivory, and therefore can be reliable cues of the presence of a host to EPNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find a clear association between the following response to heterospecific IJs and their development in a co-infected host. While EPNs are widely used in biological control in agriculture, there is increasing interest in their value as a model system for understanding animal behavior (Lewis et al, 2006;Griffin, 2012Griffin, , 2015Willett et al, 2018), genetics (Duchaud et al, 2003;Ciche and Goffredi, 2007), population biology (Stuart et al, 2006;Griffin, 2015), parasitism (Hallem et al, 2007;Castelletto et al, 2014), mutualism and ecology (Strong et al, 1999;Stock, 2005;Campos-Herrera et al, 2012;Maher et al, 2017). Here, we use EPNs to study group dynamics of a parasite and show for the first time trail following by nematodes.…”
Section: Discussionmentioning
confidence: 99%
“…For example, relative to traditional applications in aqueous sprays, applying nematodes with phoretic hosts (Shapiro-Ilan and Brown, 2013), in their infected-hosts (Dolinski et al, 2015), or in pre-infected hosts that reach cryptic habitats (Gumus et al, 2015) has resulted in increased efficacy. Certain plant volatiles may be used to enhance EPN efficacy by directing nematode behavior and enhancing infectivity (Willett et al, 2018). Furthermore, other "boosters" that directly increase EPN activity will lead to improved efficacy.…”
Section: Formulation and Application Technologymentioning
confidence: 99%